Literary Plagiarism and Copyright Protection: A Study in Academic Ethics and Copyright Law - Saed Sa'dy, Farhad; Fadhel Hamid, Abdullah; Muhammed Shareef, Murad Abid (Journal of Duhok University, 2019)
With technological development and technological information, access to information and notions has become very easy. This revolution of technology assists and encourages further enhancement and innovation in various fields, yet it might be utilized in a wrong way or it might not be used in the exact context, in which it is wrong by itself. For instance, internet and computer have facilitated the process of obtaining information from E-books and researches, at the same time it has helped to be used in wrong ways through writing books and researches.         Although technological development has helped to obtain information easily, and it has helped to gain information in a wrong way, yet through some technological programs we can ensure whether somebody has used another person’s notion or not. For instance, a program known as – Turnitin-  would give authenticity to each part of the research, displays how each part of research has been transferred, and whether plagiarism has reached to a certain percentage or not.        In the absence of a lucid and binding intellectual property rules, it would encourage people to plagiarize idea from others, or (else) it would encourage them to avoid plagiarism.  Hence, having intellectual property binding rules- in particular copyright rules- reduces plagiarism. These rules would make researchers, particularly whom are novice, to follow the rules and avoid plagiarism when they quote other’s concept.The matter in which need to be clarified is pertaining to protection which exists in copyright law. This law protects forms of expression an idea not the idea itself which refer us to origins of scientific research and scientific integrity in quoting idea and information. We dedicate this research to elaborate this protection of law through two main sections. First section explores concept, sorts, and causes of plagiarism, and second section explores copyright of authors and protecting them from some kinds of plagiarism.